Chronology, dialect and style: studies in the distribution of linguistic archaisms in early Greek hexameter poetry - McConnell, T (2019)
The chronology of early Greek hexameter poetry is obscure. Some scholars have attempted to make arguments about the relative chronology of the texts based on their differing use of certain linguistic forms. In the introductory chapter the history of the question is surveyed, and statistical arguments are used to establish which of the previously studied linguistic forms are most worthy of further study. The next three chapters are each concerned with one linguistic form – thematic genitives in -οιο and -ου; the observance and neglect of digamma; and the use of different kinds of tmesis, ‘initial’ and ‘non-initial’. In each chapter, possibly underlying factors are analysed. .